2023
DOI: 10.1002/ppp3.10471
|View full text |Cite
|
Sign up to set email alerts
|

Fire incongruities can explain widespread landscape degradation in Madagascar's forests and grasslands

Grant S. Joseph,
Colleen L. Seymour,
Andrinajoro R. Rakotoarivelo

Abstract: Societal Impact StatementThe relationship between rainfall, fire and habitat can display incongruencies. The 2021 Malagasy Grassy Biomes Workshop identified understanding fire regimes as a knowledge gap. This study pinpoints regions where anthropogenic fire has the potential to transform or has transformed habitat to treeless‐grassland, by identifying landscape‐scale, island‐wide fire anomalies across half of Madagascar. Its eastern forests burn like savannas, and central‐western grasslands burn frequently and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Indeed, rangeland degradation in the Malagasy highlands has now been linked to pasture preparation for zebu cattle (Joseph et al, 2024a), as has landscape-scale habitat degradation of both forest and grassland, as a consequence of human-associated fire anomalies that now impact half the surface area of Madagascar (Joseph et al, 2024b). savanna systems, and fire-dominated, treeless grasslands abound in regions where rainfall in other systems would support forest, and limit fires (Joseph et al, 2024b). In Madagascar, natural fire is rare (frequent anthropogenic fires diminish available substrate; Archibald et al, 2010;Bloesch, 1999).…”
Section: Giant Tortoises Selected Habitats With a High Proportion Of ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, rangeland degradation in the Malagasy highlands has now been linked to pasture preparation for zebu cattle (Joseph et al, 2024a), as has landscape-scale habitat degradation of both forest and grassland, as a consequence of human-associated fire anomalies that now impact half the surface area of Madagascar (Joseph et al, 2024b). savanna systems, and fire-dominated, treeless grasslands abound in regions where rainfall in other systems would support forest, and limit fires (Joseph et al, 2024b). In Madagascar, natural fire is rare (frequent anthropogenic fires diminish available substrate; Archibald et al, 2010;Bloesch, 1999).…”
Section: Giant Tortoises Selected Habitats With a High Proportion Of ...mentioning
confidence: 99%
“…This is critical for Aldabrachelys, and all Malagasy biota, which evolved without human-lit fire and obligate C 4 grazing ungulates. Given that half of Madagascar burns anomalously (Joseph et al, 2024b), anthropogenic fire has been identified as a central threat to the Critically Endangered Malagasy ploughshare tortoise (Astrochelys yniphora), with models supporting extinction within 50 years, even with 10-yearly fire intervals (Pedrono et al, 2004;Pedrono & Clausen, 2018). Even in fireadapted systems like the Mediterranean, tortoises cannot tolerate fire frequencies exceeding 30-year cycles (Sanz-Aguilar et al, 2011).…”
Section: Giant Tortoises Selected Habitats With a High Proportion Of ...mentioning
confidence: 99%
See 3 more Smart Citations